Mesothelioma and acceleration - Zocchetti, Carlo (La Medicina del Lavoro, 2015)
Introduction: Taking a publication  by Berry in 2007 (3) as a cue, this paper presents in didactic form the topic of acceleration of events as a consequence of a  harmful exposure and extends the proposed approach to the case of the asbestos-mesothelioma relationship. Methods: Berry’s approach was applied to lung cancer and mesothelioma data. Results: The effects of the acceleration of events are presented as a function of age at onset in exposed subjects, relative risk, scale factor, in addition to age and geographical variability of the relationship between age and mesothelioma rates. Discussion: The discussion regards the general characteristics of the method of acceleration, its meaning and interpretation, and the difficulties associated with its application in the context of diseases with low occurrence; the conditions, applicability constraints, and specific results in the case of mesothelioma; the epidemiologic meaning of  acceleration and the difficulties of its extension to individual subjects.